PROSPEK KOTA AMBON SEBAGAI AIKON KOTA MULTIKULTURAL (PELUANG dan TANTANGAN) - Hakis Hakis (IAIN Ambon, 2019)
ABSTRACT Multicultural is an interesting thing to be studied because every region and even everyone is different understanding of multiculturalism but it is sunnatullah to acknowledge its existence. But different apply multiculturalism with each other. Basically, the people of Ambon city have accepted multicultural with characteristics that differ with other people or with other cities in Indonesia. The most interesting thing in the multicultural community of Ambon city is about migrants or immigrant communities. For the people of Maluku and the people of Ambon city they are of the view that any immigrant society is still always stamped with immigrant istlah even though have children grandchild living in Ambon Maluku. Keywords: Multiculturalism, typology, equality, cultural assimilation